Understanding Microwave Surface‐Wave Sustained Plasmas at Intermediate Pressure by 2D Modeling and Experiments. Issue 4 (17th November 2016) - Georgieva, Violeta; Berthelot, Antonin; Silva, Tiago; Kolev, Stanimir; Graef, Wouter; Britun, Nikolay; Chen, Guoxing; van der Mullen, Joost; Godfroid, Thomas; Mihailova, Diana; van Dijk, Jan; Snyders, Rony; et al.
Abstract : An Ar plasma sustained by a surfaguide wave launcher is investigated at intermediate pressure (200–2667 Pa). Two 2D self‐consistent models (quasi‐neutral and plasma bulk‐sheath) are developed and benchmarked. The complete set of electromagnetic and fluid equations and the boundary conditions are presented. The transformation of fluid equations from a local reference frame, that is, moving with plasma or when the gas flow is zero, to a laboratory reference frame, that is, accounting for the gas flow, is discussed. The pressure range is extended down to 80 Pa by experimental measurements. The electron temperature decreases with pressure. The electron density depends linearly on power, and changes its behavior with pressure depending on the product of pressure and radial plasma size. Abstract : A surface‐wave sustained Ar plasma is investigated at intermediate pressure (200–2667 Pa). Two 2D self‐consistent models, a quasi‐neutral (QN) and a plasma bulk‐sheath (PS) model, are developed and benchmarked. The pressure range is extended down to 80 Pa by optical emission spectroscopy (OES) measurements. Comparison with experimental plasma characteristics available from literature for similar operating conditions is also shown and discussed.